Characterisation of adhesion receptors mediating lymphocyte adhesion to bronchial endothelium provides evidence for a distinct lung homing pathway. Issue 12 (1st December 2002) - Ainslie, M P; McNulty, C A; Huynh, T; Symon, F A; Wardlaw, A J
Abstract : Background: The lung is an important tertiary lymphoid organ and many lung diseases are associated with disordered lung immunity. Unlike the gut (α4β7 binding to MAdCAM-1) and skin (CLA+ve T cells binding to E-selectin) where the adhesion receptors involved in organ specific homing of T cells have been identified, the molecular pathways controlling lymphocyte migration to the lung are unclear. Using a modified version of the Stamper-Woodruff assay we have investigated the receptors mediating adhesion of peripheral blood lymphocytes to airway endothelium. Methods: Longitudinal frozen sections of bronchus (8 μm) obtained from lung resection specimens were incubated with T cell enriched peripheral blood mononuclear cells for 30 minutes under shaking conditions in the presence of a fluorescently labelled polyclonal anti-von Willebrand antibody to identify blood vessels. After fixation the percentage of blood vessels supporting adhesion was measured. Blocking monoclonal antibodies were used to determine the role of individual adhesion receptors in lymphocyte binding. Results: Specific cation dependent binding of lymphocytes to bronchial endothelium was observed which was significantly inhibited by antibodies against P-selectin, PSGL-1, L-selectin, LFA-1, ICAM-1 and ICAM-2 but not E-selectin, VLA-4, VCAM-1 or Mac-1. This was consistent with the pattern of endothelial expression of these receptors with strong expression of P-selectin and ICAM-1, but negligible expression of E-selectin on bronchial endothelium. Conclusion: This study suggests an important role for PSGL-1/P-selectin in T cell migration into the bronchi and provides further evidence for a pattern of recirculation for respiratory tract homing T cells distinct from the gut and skin.